ACCESSING BATAN’S LIBRARY CATALOG SYSTEM THROUGH INTERNET USING SQL SERVER 5.6 - Adelina kristiani; Susi Wagiyati P., SKom, MM. (Jurnal Sistem Informasi, 2002)
Library is an organization that collects, stores, provides books, magazines, and similar materials. BATAN P2TIK Library is managed by the Scientific Information and Documentation Division (IDI), Center for Development of Information Technology and Computing (P2TIK) BATAN PUSPITEK located in Serpong. The collection of materials and literature is in the form of books, magazines, microfiche, CD-ROM, and Current Contents. Cataloging is one of the principal activities of the library in order to manage existing collections in order to ready mix concrete and optimally efficient. Processing of library materials including descriptive cataloging and subject cataloging. Cataloging the subject is classified according to Universal Decimal Classification (UDC) and classification according to the International Nuclear Information System (INIS).For it then be made to a system of information concerning the problem. To improve library services in the BATAN, the Online Public Access system developed cataloging (OPAC), which use computer networks to display the library catalog on the BATAN Web pages on the internet. With the improvement of library catalog information access facilities BATAN through internet network, users of library services will be easier to see the information in the library, particularly on the catalog of books, because they do not need to come to the BATAN library.